Multiplatform storytelling: Are photojournalists taking advantage? - García-Taboada, Estíbaliz; Larrondo-Ureta, Ainara; Peña-Fernández, Simón (Lumina, 2021)
With the expansion of connected devices (tablets, smartphones, etc.), a leap in multiplatform technologies is occurring, bringing about changes in many areas of the communications professions. In this context, values based on flexible, multiplatform, cooperative work that takes the audience into consideration are increasingly important. Professional photography coexists with — and is even rivaled by — images taken by citizens, which are often used by the mass media. For that reason the need is greater than ever for photographers and graphic professionals who, in one way or another, adapt to the new media Using a multiple case study method, this article examines the digital resources used by photographers who have won a World Press Photo Award. It studies the ways in which they exploit the medium, extending the photographic narrative beyond the website, to promote themselves and their personal brand. The results show photographers’ preference for unidirectional communication models and superimposed strategies that have limited engagement and viralisation. The acquisition of digital expertise by photojournalists is at an intermediary stage, since the cases analyzed reveal that these professionals’ web 2.0 activity is limited or underexploited.